Everyday discrimination, co-ethnic social support and mood changes in young adult immigrants in Germany-Evidence from an ecological momentary assessment study - Heike Krüger (Elsevier, 2024)
Objective: In the context of international migration flows, Germany is the second largest receiving country of migrants in the world. The aim of this study is to investigate the momentary mood effects of discrimination experiences for young adult immigrants and which social resources can buffer negative effects. A distinction is made between the importance of inter and intra-ethnic interaction partners in processing stressors. Method: Using an ecological momentary assessment design, first-generation migrants in Germany who had recently migrated from Poland, Turkey or Syria were interviewed three times a day over seven days in June 2021 (N individuals = 976; N observations = 11,470). The timing of the short surveys was chosen at random using a signal contingent sampling method. Participants reported their momentary mood and instances of discrimination, along with information on social support perception and interaction partners during the preceding hour in the context of their everyday lives. Hybrid mixed-effects regression models were estimated and the research questions were tested with three-way interactions. Results: The results indicate that perceived social support only moderately buffers the negative effect of everyday discrimination experiences on mood. A positive main effect on mood is observed for situational variations in perceived social support as well as for support from interaction partners. Conclusion: The findings illustrate that being embedded in supportive relationships is important in everyday life, regardless of the occurrence of stressors. Furthermore, the study suggests that the level of perceived support is more important for first-generation migrants than the ethnic origin of the support provider.